One-moment post-extraction molar implantation, current issues and modern views. Literature review - Bieloziorov Ігор Володимирович; Zhegulovych Зінаїда Єгорівна (Actual Dentistry, 2024)
Annotation. In recent years, the popularity of single-moment implantation in molar areas has significantly increased, which, in turn, has contributed to the study of the terms of the successful functioning of restorations. Purpose: to investigate and systematize approaches to the theoretical substantiation and practical solution of the issues of implantation in the areas of molars with various types of post-extraction holes with obtaining primary stability and without the use of bone-plastic materials. Research materials and methods. Conducted content - analysis of scientific sources of information - search databases Google Scholar, PubMed Central, HINARI, Scopus, Research Gate, EMBASE. The received information is systematized according to the set goal. The results. It was determined that 61.7% of the first and 34% of the second molars had a sufficiently wide interradicular septum for the installation of a direct implant with a diameter of 5 mm. The frequency of implant preservation and restoration was established at 73.3%. Comparisons of 7-mm diameter implants installed directly after removal of the first molars and implants installed according to the classic protocol proved the success of both approaches within 1 year of observation. In patients with periodontitis, immediate post-extraction implantation is recommended to replace missing teeth. Cavities are classified into 5 types: type I, type II, type III, type IV (A&B) and type V, based on the level of destruction of its walls. Dynamic navigation in the lateral areas of the jaws should prevent damage to anatomical structures and ensure adequate primary stability. Conclusions. Further studies are needed to explore and develop the details of a single-stage post-extraction implantation protocol depending on the clinical setting. Keywords: one-moment post-extraction implantation of molars, immediate loading, hole of the extracted tooth, complications of implantation.